Kawasaki Disease - From History to the Present: Literature review - Tsutsui, Luísa Franco (Seven Editora, 2024)
Objectives: The text addresses the objectives of understanding Kawasaki disease in terms of its etiology, clinical manifestations, diagnosis, treatment and complications, in addition to highlighting the socioeconomic impact and future perspectives of the research. Methods: The literature review uses information from scientific studies and expert reviews to address every aspect of the disease, from its history and discovery by Tomisaku Kawasaki to the most recent therapeutic advances and ongoing research. Results: The results highlight the complexity of Kawasaki disease, including its distinct clinical manifestations, diagnostic criteria, current therapeutic options such as intravenous immunoglobulin and aspirin, and the multiple possible complications, especially those related to the cardiovascular system. Conclusions: The conclusion underscores the importance of early detection, prompt treatment, and close follow-up to improve patients' prognosis. It also points to the continued need for research to enhance understanding of the disease, develop new therapies, and improve clinical management, aiming to reduce the social and economic impact of Kawasaki disease. DOI:https://doi.org/10.56238/sevened2024.012-062